Liver X Receptors Suppress Activity of Cholesterol and Fatty Acid Synthesis Pathways To Oppose Gammaherpesvirus Replication - P. T. Lange (American Society for Microbiology, 2018)
ABSTRACT Gammaherpesviruses are oncogenic pathogens that persist in ~95% of the adult population. Cellular metabolic pathways have emerged as important regulators of many viral infections, including infections by gammaherpesviruses that require several lipid synthetic pathways for optimal replication. Liver X receptors (LXRs) are transcription factors that are critical regulators of cellular fatty acid and cholesterol synthesis pathways. Not surprisingly, LXRs are attractive therapeutic targets in cardiovascular disease. Here we describe an antiviral role for LXRs in the context of gammaherpesvirus infection of primary macrophages. We show that type I interferon increased LXR expression following infection. Surprisingly, there was not a corresponding induction of LXR target genes. Rather, LXRs suppressed the expression of target genes, leading to decreased fatty acid and cholesterol synthesis, two metabolic pathways that support gammaherpesvirus replication. This report defines LXR-mediated restriction of cholesterol and lipid synthesis as an intrinsic metabolic mechanism to restrict viral replication in innate immune cells. IMPORTANCE Fatty acid and cholesterol synthesis pathways of the host play important roles in diverse biological systems. Importantly, these two metabolic pathways are also usurped by a number of viruses to facilitate viral replication. In this report, we show that suppression of these pathways by liver X receptors in primary macrophages creates an intrinsic antiviral state that attenuates gammaherpesvirus replication by limiting viral access to the two metabolic pathways.